2011
DOI: 10.1016/j.cell.2011.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Coding-Independent Regulation of the Tumor Suppressor PTEN by Competing Endogenous mRNAs

Abstract: SUMMARY Here we demonstrate that protein-coding RNA transcripts can crosstalk by competing for common microRNAs, with microRNA response elements as the foundation of this interaction. We have termed such RNA transcripts as competing endogenous RNAs (ceRNAs). We tested this hypothesis in the context of PTEN, a key tumor suppressor whose abundance determines critical outcomes in tumorigenesis. By a combined computational and experimental approach, we identified and validated endogenous protein-coding transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
874
4
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 934 publications
(904 citation statements)
references
References 38 publications
(46 reference statements)
22
874
4
4
Order By: Relevance
“…These differential modulations of target genes results in varying levels of apoptosis or proliferation noticed in these RMS cell lines. As miRNA-mediated regulation of target genes are influenced by various factors such as p53 mutational status 43 and the presence of competing endogenous RNAs, 47 it is possible that presence or absence of these factors may influence the levels of PAX3 or CCND2 in these RMS cells.…”
Section: Discussionmentioning
confidence: 99%
“…These differential modulations of target genes results in varying levels of apoptosis or proliferation noticed in these RMS cell lines. As miRNA-mediated regulation of target genes are influenced by various factors such as p53 mutational status 43 and the presence of competing endogenous RNAs, 47 it is possible that presence or absence of these factors may influence the levels of PAX3 or CCND2 in these RMS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, certain mRNAs possess a coding-independent role in modulating the miRNA activities. [89][90][91][92] The endogenous, miRNA sponge-like transcripts also exist in plants. The first case was discovered in phosphate signaling.…”
Section: Degradome-seqmentioning
confidence: 99%
“…PTEN expression is controlled by numerous transcription factors (for example, p53, Egr-1 and CBF-1) and post-transcriptionally via oncogenic microRNAs that target PTEN mRNA 1,2 . Recently, it was shown that both mRNAs of the PTEN pseudogene, PTENP1, and competing endogenous RNAs could serve as decoys for PTEN mRNA-targeting microRNAs, inhibiting their effects on PTEN expression 7,8 . PTEN is also regulated through protein-protein interactions, the association of scaffolding proteins such as MAGI-1 and -2, NHERF and b-arrestins (b-arrs) altering its function and/or subcellular localization [9][10][11][12] .…”
mentioning
confidence: 99%